2023
DOI: 10.3390/ijms24032494
|View full text |Cite
|
Sign up to set email alerts
|

“Pulsed Hypoxia” Gradually Reprograms Breast Cancer Fibroblasts into Pro-Tumorigenic Cells via Mesenchymal–Epithelial Transition

Abstract: Hypoxia arises in most growing solid tumors and can lead to pleotropic effects that potentially increase tumor aggressiveness and resistance to therapy through regulation of the expression of genes associated with the epithelial–mesenchymal transition (EMT) and mesenchymal–epithelial transition (MET). The main goal of the current work was to obtain and investigate the intermediate phenotype of tumor cells undergoing the hypoxia-dependent transition from fibroblast to epithelial morphology. Primary breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 87 publications
0
7
0
1
Order By: Relevance
“…Notably, MET in TME fibroblasts is a fundamental process in ontogenesis and oncogenesis. It has been demonstrated that hypoxia can reprogram the fibroblast genome towards epithelial-like cells through the EMT pathway, leading cancer-associated fibroblasts to undergo intermediate states and become more aggressive epithelial-like tumor cells ( 88 ). The role of the KDM7A-DT regulation in hypoxia-associated cancer progression mechanisms is perspective in the contexts of basic tumor biology and clinical needs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, MET in TME fibroblasts is a fundamental process in ontogenesis and oncogenesis. It has been demonstrated that hypoxia can reprogram the fibroblast genome towards epithelial-like cells through the EMT pathway, leading cancer-associated fibroblasts to undergo intermediate states and become more aggressive epithelial-like tumor cells ( 88 ). The role of the KDM7A-DT regulation in hypoxia-associated cancer progression mechanisms is perspective in the contexts of basic tumor biology and clinical needs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hypoxia inhibited the tumor-suppressive function of various immune cells, thereby contributing to immunotherapy resistance [ 39 , 40 ]. It is worth noting that hypoxia can trigger angiogenesis and EMT, further exacerbating immunosuppression [ [41] , [42] , [43] , [44] ]. The CIBERSORT analysis showed that high CAFs risk scores were positively correlated to Tregs and M2 macrophage polarization, and the ssGSEA analysis showed that high CAFs risk scores were negatively correlated to CD8 + T cells and TILs, which might be the mechanism leading to immunotherapy resistance in patients with high-risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…These changes occur during embryogenesis (type 1 EMT), wound healing, tissue regeneration, fibrosis (type 2 EMT) and in cancer, where they contribute to cell stemness (plasticity), drug resistance, immune escape, and metastasis (type 3 EMT) ( Manfioletti and Fedele, 2022 ). EMT can be seen as a period of a bet-hedging—evolutionary cellular adaptation ( Jolly et al, 2018 ; Capp and Thomas, 2022 ; Jain et al, 2022 ), which diversifies mesenchymal phenotypes (cancer stemness) and increases their survival ( Mortezaee and Majidpoor, 2022 ) in changing hypoxia-induced pathophysiology ( Lee et al, 2020 ; Papale et al, 2020 ; Nushtaeva et al, 2023 ; Zhang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…EMT is reversal by the mesenchymal-to-epithelial transition (MET) ( Yang J. et al, 2020 ; Manfioletti and Fedele, 2022 ), which can be synonymous to type 2 EMT, a reparative-associated fibrotic process in response to chronic inflammation ( Marconi et al, 2021 ). The chief candidate for EMT reversal (regeneration/rejuvenation) would be the timely amelioration of hypoxia ( López-Novoa and Nieto, 2009 ; Lee et al, 2020 ; Papale et al, 2020 ; Nushtaeva et al, 2023 ; Zhang et al, 2023 ) before the establishment of dysregulation–degeneration hypoxic cell biology ( Phua, 2021 ; Rando and Jones, 2021 ) and cellular senescence ( Welford and Giaccia, 2011 ; Barabutis et al, 2018 ; Lacroix et al, 2020 ; Otero-Albiol and Carnero, 2021 ). In a review article, new approaches to alleviating hypoxia through the modulation of the vascular state in the tumor microenvironment offer promise for ovarian cancer immunotherapeutic strategies ( Klemba et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%